PELATIHAN PENGGUNAAN MEDIA SOSIAL SEBAGAI ALAT PROMOSI UKM DI PEKON GUMUK MAS (LP3K Lampung, 2021)
Community service through the PKM program aims to help provide solutions to problems faced by partners, in this case marketing issues to increase MSME turnover in Pekon Gumuk Mas, Pringsewu Regency, Lampung. The solution offered is in the form of online marketing training through social media. The indicator of success in this program is that partners who are trained are able to explain online marketing through social media well. Training related to promotion techniques through social media will also be carried out so that partners' knowledge will increase. In addition, worksheets are provided to monitor partner activities and measure the effectiveness of delivering material from the team to partners.